(untitled) (The International Journal for Scientific Research, 2023)
The stage of implementation of penal judgments is considered the key outcome of the criminal case and stands out chiefly as the most important stage of the procedures. It constitutes the highest form of justice and reflects the strength of the State in extending the application of the law by transforming the issued operative sentences into reality in which the convicted person receives his/her punishment, the plaintiff attains his right and the society succeeds in punishing those who violated the law. This stage enjoys a set of legal rules and guarantees that regulate the implementation procedures from the point of the final judgment to the actual implementation. This study aims to shed light on the implementation of the criminal rulings by the Public Prosecution Authority and determine the procedures followed in the implementation of the criminal penalties issued by the competent judicial courts and the key implementation issues that hinder the implementation phase during the practical application. Moreover, it highlights the position of the Omani legislator in this stage and the most prominent legal articles organizing this stage according to the Criminal Law. The following are the main finding of the study: 1. The Omani legislator has made the implementation of the criminal rulings issued by the criminal courts a key constituent of the work of the public prosecution and one of its various specializations in the field of public litigation. 2. extends to the implementation stage within the penal institutions. from implementing such judgments.